2019
DOI: 10.1111/1744-9987.12789
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Long‐Term Treatment With Tolvaptan to Prolong the Time Until Dialysis Initiation in Patients With Chronic Kidney Disease and Heart Failure

Abstract: The short‐term effectiveness of tolvaptan (TLV) against heart failure has been established. TLV is known to decrease the worsening of renal function more than loop diuretics. Long‐term TLV administration decreases the rate of re‐hospitalization in heart failure and prevents deterioration of kidney function. If repeated hospitalization for heart failure can be prevented in patients having concurrent chronic kidney disease (CKD), the period until dialysis initiation may be prolonged. We investigated whether long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The details and results of the systematic review and meta-analysis are summarized in the Online materials. After the systematic review, we used nine studies as references in the cost-effectiveness analysis [23][24][25][26][27][28][29][30][31] . The characteristics of the studies are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details and results of the systematic review and meta-analysis are summarized in the Online materials. After the systematic review, we used nine studies as references in the cost-effectiveness analysis [23][24][25][26][27][28][29][30][31] . The characteristics of the studies are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, in the EVEREST study, patients with severe renal dysfunction were excluded. Recently, several studies from Japan demonstrated that long-term TLV administration may be useful for the treatment of patients with CHF, especially in patients with high-dose loop diuretics and/or CKD [23][24][25][26][27][28][29][30][31] . Thus, we conducted this study to evaluate the efficacy and cost-effectiveness of long-term TLV administration in Japanese patients with CHF using a systematic review and meta-analysis and a simulation decision model.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolvaptan, a diuretic that selectively antagonizes arginine pressing V2 receptors and increases free water excretion by inhibiting water reabsorption in the collecting ducts, effectively reduces intra- and extracellular fluids, with the significant advantage of being less likely to cause deterioration in renal function [ 171 ]. Several studies have shown that treatment with tolvaptan prolongs the time to initiation of dialysis in CKD stage 4–5 patients with comorbid HF [ 172 , 173 ]. The use of tolvaptan in dialysis patients with RRF has been found to increase urine output with a favorable safety profile [ 171 , 174 ].…”
Section: Drug Treatment For Dialysis Patientsmentioning
confidence: 99%
“…The efficacy of TLV has been reported for patients with CKD in other studies[ 7 , 8 ]. Recently, the administration of TLV also demonstrated that it decreased the worsening of renal function[ 9 , 10 ]. Furthermore, TLV therapy was more effective in maintaining renal function than treatment with increasing doses of loop diuretics because TLV has a strong diuretic effect.…”
Section: Introductionmentioning
confidence: 99%